Putting terrorism in context lessons from the global terrorism database - LaFree, Gary; Dugan, Laura; Miller, Erin (Contemporary terrorism studies, 2015)
"This is the first book that provides a comprehensive empirical overview of the nature and evolution of both modern transnational and domestic terrorism, based on statistical data"-- Provided by Publisher